Desenvolvimento humano: a realidade além dos números - Camargo, Aline Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The book-report Human Development: the reality beyond the numbers addresses issues related to the Development Index (IDH), of Brazil, in a general context, and the city of Bauru, in the local context. The “IDH” is a number that serves as a comparison between countries, in order to measure the degree of economic development and the quality of life offered to the population. The classification, if high, can be readily used as a means of aggrandizement national and if low, can be used to highlight the weaknesses national. Understanding the role of media as an agent capable of promoting social debates of great importance, this book-report aims to discuss the concept of human development beyond the numbers commonly reported, prompting debates on the issue of human development: whether in relation to social issues, public policy or the role of the media in the process of contributing to the formation of public opinion. The methodology used was the data collection and the research literature, besides journalistic techniques, such as interview, report and profile

O livro-reportagem “Desenvolvimento Humano: a realidade além dos números” trata questões relacionadas ao Índice de Desenvolvimento (IDH), do Brasil, num contexto geral, e da cidade de Bauru, em âmbito local. O IDH é um número que serve de comparação entre os países, com objetivo de medir o grau de desenvolvimento econômico e a qualidade de vida oferecida à população. A classificação, se for alta, pode ser facilmente usada como meio de engrandecimento nacional, e caso seja baixa, pode ser utilizada para destacar as insuficiências nacionais. Entendendo o papel da mídia como um agente social capaz de promover debates de grande importância, este livro-reportagem tem o objetivo de discutir o conceito de desenvolvimento humano além dos números comumente divulgados, incitando debates sobre a questão do desenvolvimento humano: seja em relação à questão social, às políticas públicas ou à função da mídia no processo de contribuição para a formação da opinião pública. Como metodologia utilizou‐se coleta de dados e levantamento bibliográfico, além das técnicas jornalísticas de entrevista, reportagem e perfil
Keywords: Politicas publicas; Internet; Mídia digital; Planejamento urbano; Jornalismo eletrônico; Public policy